Interfaith Parenting: Understanding the Experiences and Challenges of Children Following One Parent’s Religion - Catherine E Fajardo; Emilou N Gallardo (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to explore the challenges experienced by children who affiliate with the religion of one parent in interfaith families within Jose Rizal, Makilala, North Cotabato. It aims to understand how these children navigate their religious identity, the emotional and social effects of choosing one religion over another, and the influence of interfaith dynamics on their personal development, beliefs, and cultural integration within family and community contexts. Methodology: This qualitative research utilized a phenomenological approach to capture the lived experiences of children from interfaith families. Data were gathered through in-depth interviews (IDI) with five participants and one focused group discussion (FGD) with another five participants. Using purposive sampling, the study was guided by two primary research questions, allowing participants to share personal reflections on their religious identity and family experiences. Main Findings: The study revealed that children from interfaith families experience challenges such as confusion in religious identity, pressure to choose one religion, and conflicts arising from differing religious and cultural practices. Despite these struggles, participants demonstrated autonomy and resilience in navigating their personal beliefs and values. Their experiences highlight the importance of open communication, acceptance, and understanding within families to reduce emotional distress and promote mutual respect for diverse faith traditions. Novelty/Originality of this study: This study provides new insights into the psychological, social, and cultural dimensions of interfaith parenting from the perspective of children who affiliate with one parent’s religion. It emphasizes the unique process of identity negotiation and emotional resilience among these children. Unlike previous studies that focused primarily on parental perspectives, this research amplifies the children’s voices, illustrating how they reconcile interreligious tensions while maintaining familial harmony. The findings contribute to the discourse on interfaith family dynamics, promoting respect, empathy, and inclusive understanding within multicultural and multireligious contexts.